Costa Rican sustainable development perspectives: The COVID-19 pandemic as a turning point? - Espinoza Cisneros, Edgar (2022)
The effects of the COVID-19 pandemic have accentuated pleas worldwide for urgent action in social, political, and environmental matters. Many of these appeals portray the pandemic as a “wake-up call” to the many long-standing problems affecting societies worldwide, including social and economic inequality, political struggles, and climate change. Indeed, calls for urgent environmental action have predominated in the wake of the pandemic, on one hand by presenting contemporary human-environment interactions as a root cause, and on the other, by comparing the pandemic effects to what could possibly occur if effective remediating actions are not taken in the short term. In this chapter, we broadly examine some relevant perspectives on the pandemic-environment relationship in the Costa Rican institutional milieu with particular focus on those who envision the pandemic as a turning point towards a more environmentally-sound development model in a country commonly portrayed as “green” and highly dependent on nature-based tourism. In so doing, we seek to provoke discussions on how these perspectives that leverage on the pandemic crisis can lead to social and environmental change significant enough to effectively redirect development pathways toward sustainability.